THE IMPACT OF DATA-DRIVEN DECISION MAKING ON MANAGERIAL EFFECTIVENESS AND BUSINESS PERFORMANCE IN EMERGING ECONOMIES - Klemens Mere (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to examine the impact of Data-Driven Decision Making (DDDM) on managerial effectiveness and business performance in emerging economies using a systematic literature review approach. The study reviewed 52 empirical studies published between 2010 and 2024 following the PRISMA protocol. Literature sources were obtained from reputable academic databases including Scopus, Web of Science, and Google Scholar. A thematic analysis was conducted to identify key patterns and relationships between data analytics adoption, managerial effectiveness, and organizational performance. The findings indicate that the implementation of DDDM consistently improves decision quality, resource allocation efficiency, and organizational agility. Managerial effectiveness plays a significant mediating role in linking analytics capabilities to enhanced business performance, including financial outcomes, operational efficiency, and innovation performance. However, the magnitude of DDDM impact is influenced by contextual factors such as digital infrastructure maturity, institutional quality, organizational culture, and human capital capability. These findings highlight the importance of developing managerial data literacy and analytics capabilities to strengthen organizational competitiveness in emerging economies.